(untitled) (Fiep Bulletin - online, 2016)
The study sought to identify the difficulties to institute humanized actions in perioperative nursing care in a school hospital. It was a descriptive research, with quantitative data analysis. The research was submitted to the Ethics Committee in Research of the Universidade do Oeste do Paraná/UNIOESTE, receiving assent. Data was collected in the Surgical Center unit (SC), from March to July 2013. The study sample consisted of 26 professionals of the nursing team, of which 25 (96%), were female, with an average age of 36.5 years old and average time of working in the Surgical Center of 06 years. The results of the study showed that the main difficulties to institute humanized actions in perioperative nursing care were: the insufficient number of employees (n=11; 25.6%); the work overload. (n=10; 23.2%); and the scarcity of material resources (n=08; 16.6%). This study identified the need of working conditions adequacy as strategies to assist in the establishment of humanized actions in the practice of preoperative nursing of the hospital under study.